1987
DOI: 10.1002/srin.198700230
|View full text |Cite
|
Sign up to set email alerts
|

Paper, honoured with the Sir Charles Hatchett Award by the Institute of Metals, London: Developments in high speed tool steels

Abstract: This paper describes a research programme at the Austrian School of Mines (Montanuniversität) at Leoben, carried out since 1981 in cooperation with the Max‐Planck‐Institute for metals research in Stuttgart, on the fundamentals of alloy design for high speed tool steels. Among the results, the development of niobium‐alloyed grades has an important place. Controlled solidification studies with a gradient technique have clarified the influence of various alloying elements on the as‐cast microstructure of ledeburi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It also influences the volume fraction of the eutectic colonies. [22][23][24][25][26][27][28] The positive effects of the higher cooling rate are limited to the regions situated nearer the surface of the ingot (Figure 3(a)), but in the central regions of the ingot, typical regions exhibit greater and lesser concentrations of eutectic colonies (Figure 4(a)). The microstructure in Figure 5(a) was obtained with a laboratory simulation [20] of the solidification process carried out on the Gleeble 1500D thermomechanical simulator, employing a relatively low cooling rate of 0.16 K/s.…”
Section: B Influence Of Cooling Rate On the Microstructuresmentioning
confidence: 99%
“…It also influences the volume fraction of the eutectic colonies. [22][23][24][25][26][27][28] The positive effects of the higher cooling rate are limited to the regions situated nearer the surface of the ingot (Figure 3(a)), but in the central regions of the ingot, typical regions exhibit greater and lesser concentrations of eutectic colonies (Figure 4(a)). The microstructure in Figure 5(a) was obtained with a laboratory simulation [20] of the solidification process carried out on the Gleeble 1500D thermomechanical simulator, employing a relatively low cooling rate of 0.16 K/s.…”
Section: B Influence Of Cooling Rate On the Microstructuresmentioning
confidence: 99%
“…At natural cooling rates, the niobium rich MC carbides precipitated straight from melt will grow up to a larger scale to the end of solidification , which obviously affecting the toughness to a high degree. It is reported that high cooling rate can increase the heterogeneous nucleation and depress the growth of primary NbC carbides .…”
Section: Introductionmentioning
confidence: 99%
“…3) As well recognized, the cutting performance of high-speed steels is intrinsically related to the characteristics of the carbide precipitates, such as size, amount, morphology, type and spatial distribution. 4) Large carbides not only deteriorate the hot workability of high-speed steels, 5) but also promote the nucleation of microcracks during service. 4,6) Similar to many other high-speed steels, two main types of eutectic carbides are formed during the solidification of M42 steel, i.e., M 2 C carbide and M 6 C carbide, and distributed in the interdendritic regions in the form of a continuous network.…”
Section: Introductionmentioning
confidence: 99%
“…4) Large carbides not only deteriorate the hot workability of high-speed steels, 5) but also promote the nucleation of microcracks during service. 4,6) Similar to many other high-speed steels, two main types of eutectic carbides are formed during the solidification of M42 steel, i.e., M 2 C carbide and M 6 C carbide, and distributed in the interdendritic regions in the form of a continuous network. [7][8][9][10] As-cast MC carbide is occasionally observed in M42 steel.…”
Section: Introductionmentioning
confidence: 99%